(untitled) (Research, Society and Development, 2022)
Given the above, the study aims to describe patient care in the postoperative period of permanent cardiac pacemaker implantation. This is an integrative literature review carried out using the Scientific Electronic Library Online (SciELO), Latin American and Caribbean Literature in Health Sciences (LILACS) and Medical Literature Analysis and Retrieval System Online (MEDLINE) databases. of the following Health Sciences Descriptors (DeCS): “artificial pacemaker” and “postoperative care”. Combined with each other by the Boolean operator AND. As inclusion criteria: articles available in full, in Portuguese, Spanish and English, that addressed the theme, in the last five years (2017-2022). As exclusion criteria: articles that did not contemplate the theme and repeated studies in the databases. 266 articles were found, after the combined search of descriptors and operators, 9 articles were selected to compose the final sample. The nurse must welcome the patient safely, offering safe care and being the link between the various participants of the multidisciplinary team. It is extremely necessary that the tips on the perfect use of the pacemaker be defined preoperatively by the nurse, so that he can help the patient’s autonomy and clarify his doubts, since he is often informed about the meaning and need for support a surgical procedure, but they no longer provide statistics on the care you should have in the postoperative period.